RANCANG BANGUN SISTEM PELAYANAN MASYARAKAT (SURAT PENGANTAR DESA) DI DESA ORO– ORO OMBO DENGAN METODE PERSONAL EXTREME PROGRAMMING - Rizky Habibullah Fuady (Jurnal Repositor, 2023)
Abstract Oro - Oro Ombo Village is a village located in Batu District, Batu City, East Java. Until now, the Oro - Oro Ombo village government still uses a manual system for community services, especially in the village cover letter service. Thus, a system is needed that can manage the process of making village cover letters quickly and precisely. A software development method that can meet these needs is Personal Extreme Programming. Personal Extreme Programming is a design development method to be implemented by a single developer or himself. Personal Extreme Programming is a development of the Extreme Programming method which in practice is done by several developers. The purpose of this study is to develop a Personal Extreme Programming method in village management in the field of village cover letter making services. The system that will be built in this study is a village service system. The needs of the client are collected at the requirements stage, then the development process is continued with iteration planning and prioritization of needs with discussions between developers and clients. The system development process is carried out iteratively, if there is a change in needs, then re-planning is carried out. Based on the results of this study, Personal Extreme Programming can be implemented in this case, the flexibility of PXP and interaction with the client when determining the basic needs of the system is clearly obtained, so that the system development process remains directed and the results are in accordance with the needs of the client. Keywords: system, Extreme Programming, Personal Extreme Programming, needs, mail service.